Indonesian Government Policies In Overcoming Post-Covid-19 Unemployment From An Islamic Economic Perspective - Hasbi Abdul Al Wahhab KH; Dea Dahlia; Muhammad Nur Rianto Al Arif (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2023)
As an Important macroeconomic indicator, unemployment is a serious problem for Indonesian society. This article examines the government's support in reducing unemployment after COVID-19 from an Islamic economic perspective. This research uses a qualitative method using library research methods. The research results show that in the last 5 years, the unemployment rate in Indonesia has gradually decreased. The Open Unemployment Rate (TPT) for February 2023 was 5.45%, down 0.38 of a percentage point from February 2022. Unemployment is viewed as an unfortunate thing from an Islamic perspective as Islam constantly encourages people to work and avoid being unemployed. The government combats joblessness through various approach including international monetary, revenue, finance, and economic policies. These included allocating special funds to combat Covid-19, implementing tax incentives, facilitating relief in credit repayments, rapidly adopting policies aimed at reducing reductions in employment-related social security contributions, expanding social support, and providing skills and productivity training through Balai Latihan Kerja (BLK). WORK TRAINING CENTERS (BLK). The government also implemented several programs to improve employment opportunities, set up consultation services, provided information and complaint channels for workers regarding occupational safety and health (OSH) in the workplace, and issued pre-employment cards to improve the skills and outlook of job seekers. The weakness in this research is that uses more theory, so future researchers are advised to study it more deeply.